2013
DOI: 10.1080/03602559.2012.735739
|View full text |Cite
|
Sign up to set email alerts
|

SEBS-g-MAH as a Reactive Compatibilizer Precursor for PP/PTT/SEBS Ternary Blends: Morphology and Mechanical Properties

Abstract: This article highlights the effect of using maleic anhydride-assisted SEBS compatibilizer precursor on the morphology and mechanical properties of the polypropylene (PP)/poly (trimethylene terephthalate) (PTT)/poly(styrene-b-(ethylene-co-butylene)-b-styrene) (SEBS) 70/15/15 ternary blends. In all ternary blends, the amounts of PP and PTT, respectively as the matrix and the primary minor components were kept constant at 70 and 15 wt%; in turn, the amount of constituent polymers within the secondary minor phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This shortcoming roots in large difference in their polarities [13,14]. As a consequence of this, PP/PET blends reveal poor mechanical properties because of insufficient interfacial adhesion between components, and hence need to be strengthened by a compatibilizing agent [15][16][17].…”
Section: Introductionmentioning
confidence: 97%
“…This shortcoming roots in large difference in their polarities [13,14]. As a consequence of this, PP/PET blends reveal poor mechanical properties because of insufficient interfacial adhesion between components, and hence need to be strengthened by a compatibilizing agent [15][16][17].…”
Section: Introductionmentioning
confidence: 97%
“…Compatibilizer molecules, in general, are assumed to be inhomogeneously distributed across the interface. The molecular nature of the compatibilizer, that is, chain length and number of functional units per chain, determines the final particle size (or characteristic size of the phases) and, subsequently, the degree of change in morphological and mechanical characteristics . Overall, a desired level of interfacial adhesion is considered to be present when the compatibilizer provides sufficient molecular entanglement and penetration into the interface of each phase .…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of the researches have been focused on the direct use of polar elastomers or functionalized elastomers. These elastomers include maleic anhydride grafted ethylene-propylene-diene copolymer (EPDM-g-MA) [13][14][15] , maleic anhydride grafted acrylonitrile-butadiene-styrene (ABS-g-MA) [16,17] , maleic anhydride grafted styreneethylene=butadiene-styrene (SEBS-g-MA) [18] , maleic anhydride grafted poly(ethylene-octene) (POE-g-MA) [19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of the researches have been focused on the direct use of polar elastomers or functionalized elastomers. These elastomers include maleic anhydride grafted ethylene-propylene-diene copolymer (EPDM-g-MA) [13][14][15] , maleic anhydride grafted acrylonitrile-butadiene-styrene (ABS-g-MA) [16,17] , maleic anhydride grafted styreneethylene=butadiene-styrene (SEBS-g-MA) [18] , maleic anhydride grafted poly(ethylene-octene) (POE-g-MA) [19,20] .In addition, the other toughening methods of PTT are related to the use of the vulcanized thermoplastics and coreshell particles. For example, Savadekar and Mhaske [21] introduced vulcanized thermoplastics based on polypropylene (PP) and EPDM, i.e., PP-g-EPDM, into PTT and found that the impact strength was significantly increased with the increase of PP-g-EPDM content.…”
mentioning
confidence: 99%